If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(y + 2) = -2(y + 4) + -1y Reorder the terms: -3(2 + y) = -2(y + 4) + -1y (2 * -3 + y * -3) = -2(y + 4) + -1y (-6 + -3y) = -2(y + 4) + -1y Reorder the terms: -6 + -3y = -2(4 + y) + -1y -6 + -3y = (4 * -2 + y * -2) + -1y -6 + -3y = (-8 + -2y) + -1y Combine like terms: -2y + -1y = -3y -6 + -3y = -8 + -3y Add '3y' to each side of the equation. -6 + -3y + 3y = -8 + -3y + 3y Combine like terms: -3y + 3y = 0 -6 + 0 = -8 + -3y + 3y -6 = -8 + -3y + 3y Combine like terms: -3y + 3y = 0 -6 = -8 + 0 -6 = -8 Solving -6 = -8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3x^2=1 | | (19x+6)(20x)= | | 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 | | .5x+16(x+2)=48.5 | | 5x-11=10+12x | | (x+2x^3-3)/(x-1) | | x^4-9x^2-52=0 | | 3+y=19 | | 2z-3-2(1+z)=-5 | | Y=-2/5 | | 2x/3-2=4 | | -7x+1=57 | | x/4.6=-2.5 | | 4X^2+8X-180=0 | | (C+5)/2=18 | | 2(x-7)=35 | | 5y^3-20y^2+y-4= | | x^2-3x+85=0 | | x-2/3=2x+11 | | 5u+5(1+u)=u+8 | | s+x=16 | | x^3+x-17=0 |